The Implementation of Singing Activities in Developing Social Behavior of Children Aged 5-6 Years - Ratih Juniati; Fadillah Putri Nadia (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
Children's social behavior has not developed as expected; seven children have not been able to play with their peers and have not been able to respect their friends when singing. Singing can attract children's attention and be the right stimulus to develop children's social emotions. This research aims to discover that singing can create social behavior in children aged 5-6. The approach used is a qualitative approach. With a descriptive type of research, this research was conducted at Teratai UNM Integrated PAUD. The population in this study was all Group B and the sample of this research was Group B2. The research subjects were one teacher and 14 students. Data collection techniques in this research used observation, interview, and documentation techniques. The data analysis technique used was descriptive analysis. The research results show changes in children's social behavior, including playing with peers, respecting friends when singing, and having good manners. Initially, there was no visible change in the child's social behavior. Still, after implementing the singing activity, it was seen that the child experienced good changes in the attitude toward playing with peers, respecting friends when singing, and getting to know manners and manners so this activity is very appropriate to be recommended in the use of learning activities in teaching and learning process in class.